2012
DOI: 10.1371/journal.pone.0033587
|View full text |Cite
|
Sign up to set email alerts
|

Role of Trehalose in Salinity and Temperature Tolerance in the Model Halophilic Bacterium Chromohalobacter salexigens

Abstract: The disaccharide trehalose is considered as a universal stress molecule, protecting cells and biomolecules from injuries imposed by high osmolarity, heat, oxidation, desiccation and freezing. Chromohalobacter salexigens is a halophilic and extremely halotolerant γ-proteobacterium of the family Halomonadaceae . In this work, we have investigated the role of trehalose as a protectant against salinity, temperature and desiccation in C. salexigens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 73 publications
0
30
0
2
Order By: Relevance
“…Probably, trehalose adds stringency by shielding attractive forces between particles in a high salt concentration environment and maintaining enough repulsion to keep the particles apart. In plants and bacteria, trehalose has been reported to confer tolerance to high salt stress414243.…”
Section: Discussionmentioning
confidence: 99%
“…Probably, trehalose adds stringency by shielding attractive forces between particles in a high salt concentration environment and maintaining enough repulsion to keep the particles apart. In plants and bacteria, trehalose has been reported to confer tolerance to high salt stress414243.…”
Section: Discussionmentioning
confidence: 99%
“…Introduction of pHYDROX2 in wild-type cells switched the synthesis to hydroxyectoine, which became the major compatible solute, followed by glutamate, trehalose, and minor amounts of glucosylglycerol and ectoine. The presence of trehalose in the wild type overexpressing hydroxyectoine at 37°C was unexpected, as this sugar is synthesized by C. salexigens in response to heat stress or when ectoine is absent (18). This apparent induction of trehalose synthesis by hydroxyectoine will be investigated in a further work.…”
mentioning
confidence: 91%
“…Denaturation of cytoplasmic proteins is another common consequence of these stresses (56,58). Trehalose, which facilitates protein folding and prevents aggregation of denatured proteins (59,60), is widely recognized as a thermoprotectant (61)(62)(63). Indeed, we showed that the missense mutation in otsA, encoding the key enzyme for trehalose synthesis (64,65), partly accounts for the improved thermotolerance of the evolved strains.…”
Section: Discussionmentioning
confidence: 83%